Anionic food color tartrazine enhances antibacterial efficacy of histatin-derived peptide DHVAR4 by fine-tuning its membrane activity. (2nd March 2020) - Ricci, Maria; Horváti, Kata; Juhász, Tünde; Szigyártó, Imola; Török, György; Sebák, Fanni; Bodor, Andrea; Homolya, László; Henczkó, Judit; Pályi, Bernadett; Mlinkó, Tamás; Mihály, Judith; et al.
Abstract: Here it is demonstrated how some anionic food additives commonly used in our diet, such as tartrazine (TZ), bind to DHVAR4, an antimicrobial peptide (AMP) derived from oral host defense peptides, resulting in significantly fostered toxic activity against both Gram-positive and Gram-negative bacteria, but not against mammalian cells. Biophysical studies on the DHVAR4–TZ interaction indicate that initially large, positively charged aggregates are formed, but in the presence of lipid bilayers, they rather associate with the membrane surface. In contrast to synergistic effects observed for mixed antibacterial compounds, this is a principally different mechanism, where TZ directly acts on the membrane-associated AMP promoting its biologically active helical conformation. Model vesicle studies show that compared to dye-free DHVAR4, peptide–TZ complexes are more prone to form H-bonds with the phosphate ester moiety of the bilayer head-group region resulting in more controlled bilayer fusion mechanism and concerted severe cell damage. AMPs are considered as promising compounds to combat formidable antibiotic-resistant bacterial infections; however, we know very little on their in vivo actions, especially on how they interact with other chemical agents. The current example illustrates how food dyes can modulate AMP activity, which is hoped to inspire improved therapies against microbial infections in the alimentary tract. Results also imply that the structure and function of natural AMPs could be manipulated by small compounds, which may also offer a new strategic concept for the future design of peptide-based antimicrobials.